ANALYSIS OF STUDENT LEARNING MOTIVATION AFTER APPLIED STUDENT ACTIVITY-BASED LEARNING STRATEGY (PBAS) DURING PANDEMIC COVID-19 - Sri Cacik; Ferry Yudha Pratama (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2022)
During the Covid-19 pandemic, it is necessary to choose the right learning strategy. Thus, students' learning motivation does not decrease. This research aimed to describe students' learning motivation in science subjects with Biotechnology material after the strategy of Student Activity-Based Learning was applied. This research is quantitative and descriptive. The research subjects were 64 students of 9th grade SMP Muhammadiyah 9 Bojonegoro for 2020/2021. The research instrument used was a learning motivation questionnaire which contains 20 questions divided into six indicators, namely intrinsic orientation goals, extrinsic orientation goals, task values, trust control for learning, self-confidence, and anxiety levels. Measurement of each question uses a Likert scale, namely (1) strongly disagree, (2) disagree, (3) undecided, (4) agree, and (5) strongly agree. The results of the research were calculated using the percentage and average score. Furthermore, it is described in the form of categories. The results showed that the average score of the first indicator to 6th in a row were 3.78; 3.29; 3.74; 3.61; 3.45; and 3.56. The average score of all indicators of student learning motivation was 3.57, which has a good category. Based on the research results, it can be concluded that the student's learning motivation in the science subject with Biotechnology material is categorized as good after applying the strategy of Student Activity-Based Learning.